Virucidal activity of three standard chemical disinfectants against Ebola virus suspended in tripartite soil and whole blood - Hulda R. Jonsdottir; Daniel Zysset; Nicole Lenz; Denise Siegrist; Yelena Ruedin; Sarah Ryter; Roland Züst; Yannick Geissmann; Rahel Ackermann-Gäumann; Olivier B. Engler; Benjamin Weber (Scientific Reports, 2023)
Abstract Proper disinfection and inactivation of highly pathogenic viruses is an essential component of public health and prevention. Depending on environment, surfaces, and type of contaminant, various methods of disinfection must be both efficient and available. To test both established and novel chemical disinfectants against risk group 4 viruses in our maximum containment facility, we developed a standardized protocol and assessed the chemical inactivation of the two Ebola virus variants Mayinga and Makona suspended in two different biological soil loads. Standard chemical disinfectants ethanol and sodium hypochlorite completely inactivate both Ebola variants after 30 s in suspension at 70% and 0.5% v/v, respectively, concentrations recommended for disinfection by the World Health Organization. Additionally, peracetic acid is also inactivating at 0.2% v/v under the same conditions. Continued vigilance and optimization of current disinfection protocols is extremely important due to the continuous presence of Ebola virus on the African continent and increased zoonotic spillover of novel viral pathogens. Furthermore, to facilitate general pandemic preparedness, the establishment and sharing of standardized protocols is very important as it allows for rapid testing and evaluation of novel pathogens and chemical disinfectants.